Autologous Hematopoietic Stem Cell Transplantation in Active Multiple Sclerosis: A Real-world Case Series. (31st August 2021) - Nicholas, Richard S.; Rhone, Elijah E.; Mariottini, Alice; Silber, Eli; Malik, Omar; Singh-Curry, Victoria; Turner, Ben; Scalfari, Antonio; Ciccarelli, Olga; Sormani, Maria P.; Olavarria, Eduardo; Mehra, Varun; et al.
Abstract : Objective: To examine outcomes in people with multiple sclerosis (PwMS) treated with autologous hematopoietic stem cell transplantation (AHSCT) in a real-world setting. Methods: This was a retrospective cohort study of PwMS treated with AHSCT at 2 centers in London, UK, consecutively between 2012 and 2019 who had ≥6 months of follow-up or died at any time. Primary outcomes were survival free of multiple sclerosis (MS) relapses, MRI new lesions, and worsening of Expanded Disability Status Scale (EDSS) score. Adverse events rates were also examined. Results: The cohort includes 120 PwMS; 52% had progressive MS (primary or secondary) and 48% had relapsing-remitting MS. At baseline, the median EDSS score was 6.0; 90% of the evaluable cases showed MRI activity in the 12 months preceding AHSCT. Median follow-up after AHSCT was 21 months (range 6–85 months). MS relapse-free survival was 93% at 2 years and 87% at 4 years after AHSCT. No new MRI lesions were detected in 90% of participants at 2 years and in 85% at 4 years. EDSS score progression–free survival (PFS) was 75% at 2 years and 65% at 4 years. Epstein-Barr virus reactivation and monoclonal paraproteinemia were associated with worse PFS. There were 3 transplantation-related deaths within 100 days (2.5%), all after fluid overload and cardiac or respiratory failure. Conclusions: Efficacy outcomes of AHSCT in this real-world cohort are similar to those reported in more stringently selected clinical trial populations, although the risks may be higher. Classification of Evidence: This study is rated Class IV because of the uncontrolled, open-label design.